2000-luvun suomalaisten satuelokuvien musiikillinen kerronta ja yhteiskunnalliset teemat: esimerkkinä elokuva Pelikaanimies (2004) - Qvick Sanna (Suomen musiikkitieteellisen seuran julkaisu, 2022)
Musical narratives and social themes in Finnis fairytale films of the 21st century exemplified by Pelican man (2004)
The number of fairytale films for children has increased noticeably in Finland since the dawn of the twenty-first century. It is thus fair to say that such films have become a prominent area in children's audiovisual culture, and furthermore that these films representa significant socio-cultural force in today's society. This is true not onlybecause of their growing numbers, but also because of recent changes in their themes: the films cover subjects from childrenäs everyday lives (e.g. friendship, parent's divorce or other family issues) to wider social questions in surrounding society and the world (e.g. refugees, otherness, climatechange, environmental crises). These changes have also had an impact on the soundtracks of fairytale films. The flms are characterised by a comprehensive sound design that uses film music like sound effects and sound effect like music and draws freely on the various traditions of film music practices as well as from various musical genres. In this article I present an overview of the narrative strategies in the music for Finnish fairytale films since 2000, and discuss the socio-cultural themes of the films, in particular, how the themes can be heard in the soundtracks. As an example of the socio-culturally critical children's fairytale films, the soundtrack of Pelikaanimies (in English Pelicanman, dir 2004 by Liisa Helminen) is analysed in some detail.